FACTORS INFLUENCING UTILIZATION OF INTRAUTERINE CONTRACEPTIVE DEVICES AMONG WOMEN OF REPRODUCTIVE AGE AT ENTEBBE REGIONAL REFERRAL HOSPITAL, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - Nakate, Kevin; Bantia, Mercy; Naggulu, Immaculate Prosperia; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2025)
Background. Intrauterine devices are one of the long-acting, safe and effective methods of contraception in women of reproductive age across the world with a safety percentage of 89 %. The purpose of this study was to assess the factors influencing utilization of intrauterine contraceptive device contraception among women of reproductive age at Entebbe regional referral hospital, Entebbe municipality Wakiso district. Methods. A descriptive-cross sectional design. Quantitative methods of data collection were employed. A self-administered questionnaire was used to collect data from a sample size of 30 respondents. Data was collected using a simple random sampling method. Result. Most 13(43.3%) of the respondents were between 26 and 30 years of age, 11(36.7%) had a primary level of education, 12(40%) had two children, 24(80%) had only one sexual partner and 18(60%) had a low family level of income. Concerning health facility-related factors; more than half 17(56.7%) take four hours and more waiting for family planning services, 16(53.3%) mentioned that health care providers do not recommend the use of intrauterine devices, 18(60%) do not receive health education about the use of intrauterine devices at the facility. Conclusion. The Individual factors were; age, level of education, number of children, weight, number of sexual partners, and family level of income. The health facility-related factors were; waiting time, health care providers’ recommendations, health education, availability of health facilities in community and availability of intra uterine devices. Recommendations. Healthcare workers should implement strategies to minimize waiting times for contraceptive services, including intra-uterine device insertion, and strengthen health education programs within the hospital to raise awareness about the benefits and availability of intra-uterine devices